Beam test of cold-formed steel built-up open section with different number and position of perforations - Nur Syahidah, Muhammad (2018)
A cold-formed steel member include such products as purlins and girts for the construction of metal buildings, studs and joists for light commercial and residential construction, supports for curtain wall systems and also as a formed deck for the construction of floors and roof. Cold-formed steel comes with various type of section based on their function and purpose in construction work. This research will investigate the failure mode regarding the buckling behavior and the ultimate load of built-up cold-formed steel members with circular web holes. Structural members of cold-formed steel usually come with the presence of perforations. Perforation is a hole or opening that is made on the cold-formed steel to ease construction work. A total of 5 specimens with 20 mm holes diameters were tested under four-point bending test. The built-up open sections were assembled by self-tapping screws from either two lipped channels. Each member has nominal thickness of 1.2 mm, beam length of 1600 mm and supported with roller at both end. Reduction of ultimate loading and localized failure due to the presence of holes in the web plates of beams was observed in the tests. The result of this experiment shows that the ultimate load of each sample varies greatly on the number and position of perforation. The result is presented in two sections which are load vs displacement and buckling behavior.